Medication use in aged care residents in the last year of life: A scoping review. (July 2020) - Aitken, Charlotte; Boyd, Michal; Nielsen, Lorraine; Collier, Aileen
Background: A substantial number of older adults die in residential aged care facilities, yet little is known about the characteristics of and how best to optimise medication use in the last year of life. Aim: The aim of this review was to map characteristics of medication use in aged care residents during the last year of life in order to examine key concepts related to medication safety and draw implications for further research and service provision. Design: A scoping review following Arskey and O'Malley's framework was conducted using a targeted keyword search, followed by assessments of eligibility based on title and content of abstracts and full papers. Following Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines, the scoping review protocol was prospectively registered to the Open Science Framework on 27 November 2018. Data Sources: We searched MEDLINE, EMBASE, AMED, CINAHL and Cochrane databases to identify peer-reviewed studies published between 1937 and 2018, written in English and looking at medication use in individuals living in aged care facilities within their last year of life. Results: A total of 30 papers were reviewed. Five key overarching themes were derived from the analysis process: (1) access to medicines at the end of life, (2) categorisation and classes: medicines and populations, (3) polypharmacy and total medication numbers, (4) use of symptomatic versus preventive medications and (5) 'inappropriate' medications. Conclusion: Number of prescriptions or blunt categorisations of medications to assess their appropriateness are unlikely to be sufficient to promote well-being and medication safety for older people in residential aged care in the final stages of life.